2014
DOI: 10.3389/fnut.2014.00010
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of a Healthy Snack (Fruit) Versus an Unhealthy Snack (Chocolate/Crisps) on Subjective Reports of Mental and Physical Health: A Preliminary Intervention Study

Abstract: Background/Aims: Recent research has shown associations between type of snack and wellbeing. These studies have been cross-sectional and the aim of the present research was to examine this topic using an intervention study.Methods: A between-subjects intervention study was carried out. Volunteers (100 students, mean age = 19.00 years; 27 male, 73 female) completed online questionnaires measuring anxiety and depression, fatigue, somatic symptoms, cognitive difficulties, and distress at baseline. They were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 47 publications
2
46
0
1
Order By: Relevance
“…Most of the current evidence is correlational, but experimental and micro‐longitudinal research suggests a causal link between FV and well‐being. Two recent intervention studies showed that daily fruit consumption reduced self‐reported anxiety across a 10‐day period (Smith & Rogers, ), and that eating two kiwifruits per day resulted in significant improvements among emotionally vulnerable men in self‐reported ‘vigour,' which included reports of feeling cheerful, energetic, lively, and full of pep (Carr et al ., ). Similar experimental effects have been found for high doses of vitamins B and C, which are found abundantly in FV (Kennedy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Most of the current evidence is correlational, but experimental and micro‐longitudinal research suggests a causal link between FV and well‐being. Two recent intervention studies showed that daily fruit consumption reduced self‐reported anxiety across a 10‐day period (Smith & Rogers, ), and that eating two kiwifruits per day resulted in significant improvements among emotionally vulnerable men in self‐reported ‘vigour,' which included reports of feeling cheerful, energetic, lively, and full of pep (Carr et al ., ). Similar experimental effects have been found for high doses of vitamins B and C, which are found abundantly in FV (Kennedy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Among them, there are specific nutrients, which are known as such that may be related to mental health and for which fruit and vegetables are indicated as a valuable sources in diet, such as complex carbohydrates [20] and fiber [21], being associated with glycemic index [22], C vitamin [23], B vitamins [24], carotenoids [25], potassium [26], and polyphenols [27]. The other explanations are associated with either possibility of reverse mechanism (higher level of mental health may promote better diet, including higher fruit and vegetables intake) [28], or psychological explanation (following better diet, including higher fruit and vegetables intake may promote more positive emotions and better mental health) [29].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] There have also been 3 important small randomized controlled trials on nutritional counseling and on the provision of healthy food and snacks, [20][21][22] which find some evidence that a higher intake of fruits and vegetables may be associated with improved psychological health (as well as physical health). Another set of writings has tried to understand obesity and its links to subjective well-being.…”
mentioning
confidence: 99%